ADAWATUL ISTIFHAM DALAM NOVEL ‘ALA MAIDATIN DA’ISY KARYA ZAHRA ‘ABDULLAH - Miftahul Khoer (Hijai - Journal on Arabic Language and Literature, 2025)
This study examines Adawāt al-Istifhām in the sentences contained in a novel titled ‘Alā Mā’idatin Dā’ish by Zahra ‘Abdullah. A total of 166 words categorized as Adawāt al-Istifhām were found, spread across various sentences. The purpose of this research is to describe the forms and meanings of Adawāt al-Istifhām from the perspective of ‘Ilm al-Ma‘ānī, as well as their I‘rāb Maḥallī from the perspective of ‘Ilm al-Naḥw. This study applies a qualitative descriptive method with a library research design. The data sources of this research consist of sentences in the novel ‘Alā Mā’idatin Dā’ish that contain Adawāt al-Istifhām. Data collection was carried out through comprehensive reading of the identified data, which was then analyzed using existing theoretical approaches, classified, and interpreted thoroughly before presenting the conclusions. The results of the study are as follows: (1) The Adawāt al-Istifhām found in the novel ‘Alā Mā’idatin Dā’ish by Zahra ‘Abdullah consist of ten (10) forms, namely: limādhā (لماذا), hal (هل), hamzah (أ), ayna (أين), mādhā (ماذا), kam (كم), kayfa (كيف), matā (متى), mā (ما), and man (من). (2) Their meanings are both literal (ḥaqīqī) and figurative (majāzī), including: amazement, prohibition, persuasion, wishing, equivalence, denial, command, transformation, reprimand, belittlement, warning, delaying, explanation, arrogance, and comparison. (3) The I‘rāb Maḥallī includes: having no syntactic position, occupying the position of jarr, functioning as an adverb of place (ẓarf makān), as a subject (mubtada’), and as a fronted predicate (khabar muqaddam). This research provides opportunities for other researchers to use it as a reference and comparison for future studies. Keywords: Alā Mā’idatin Dā’ish, Zahra ‘Abdullah, Adawāt al-Istifhām, Nahw, Ma‘ānī